2022
DOI: 10.1371/journal.pone.0270993
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of multidrug-resistant Listeria monocytogenes in milk and milk product and One Health perspective

Abstract: The occurrence and the antibiogram signatures of Listeria monocytogenes (Lm) recovered from 65 milk samples and its products within the Eastern Cape province were examined. The EN ISO 11290:2017 procedures Parts 1 and 2 described by the International Organization for Standardization for the enumeration and isolation of Lm was adopted for the study. Lm was detected in 18.46% of all the samples examined, and the strains recovered from the samples belong to serotypes 4b and 1/2b. The virulence determinants includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 73 publications
0
20
0
1
Order By: Relevance
“…Because the isolates in this study were recovered from geographically and temporally separate occasions, it remains to be tested as to their antibiotic susceptibility phenotypes as genotypes and phenotypes do not always coincide. Although antibiotic resistance in general is not a serious issue in Listeria , multidrug-resistant Listeria do occur in food ( Kayode and Okoh, 2022a , b ). Thus, it is important to monitor the prevalence of antibiotic resistance genes, especially in hypervirulence clonal groups.…”
Section: Discussionmentioning
confidence: 99%
“…Because the isolates in this study were recovered from geographically and temporally separate occasions, it remains to be tested as to their antibiotic susceptibility phenotypes as genotypes and phenotypes do not always coincide. Although antibiotic resistance in general is not a serious issue in Listeria , multidrug-resistant Listeria do occur in food ( Kayode and Okoh, 2022a , b ). Thus, it is important to monitor the prevalence of antibiotic resistance genes, especially in hypervirulence clonal groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 80.8% of L. monocytogenes isolates showed the ability to form biofilm at 37°C, and of these isolates, 34.6% showed strong biofilm-forming ability. The biofilmforming potential of L. monocytogenes is influenced by the presence of virulence genes (Price et al, 2018) and antimicrobial resistance (Kayode and Okoh, 2022). MDR strains were associated with strong biofilm-forming ability, which might be attributed to the higher tolerance of these isolates to disinfectants and antimicrobials (Doulgeraki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Adem et al (11) also confirmed the presence of high quantities of disease-causing fungi and parasites in a large component of raw milk sourced from local animal breeders in the country. Scientific reports on multi-drug resistant bacteria are available in the country [12]. Thonda et al (13) reported the prevalence of antibiotic resistant bacteria in raw cow milk samples in Osun state, Nigeria.…”
Section: Introductionmentioning
confidence: 99%